Phytochemical, Antimicrobial and Antioxidant properties of an invasive weed - Chromolaena odorata (L.) King & Robinson - N Nanadini; P Nagababu; Vanga Umamaheswara Rao; N Venugopal (International Journal of Phytomedicine, 2014)
Chromolaena odorata (L.) King & Rob. native to Tropical America belongs to Asteraceae family, is an invasive weed to Indian context. It spreads all across and started engulfing the forest fringes in Andhra Pradesh and other several states in India. With a view to positive utilization of the invasive weeds, the present work was initiated to study the phytochemical screening, antibacterial and antioxidant, activities of ethyl acetate, acetone, methanol and aqueous extracts of Chromolaena odorata leaves. Phoytochemicals like Saponins, Alkaloids, Flavonoids, Steroids and Tannins were present in the ethyl acetate and aqueous extracts where as acetone and methanol extracts were positive for Flavonoids and Alkaloids. The ethyl acetate and aqueous extracts showed relatively more antibacterial activity than positive control streptomycin by exhibiting larger zone of diameter against Proteus mirabilis MTCC-425, Bacillus megaterium MTCC-428 and Bacillus subtilis MTCC-441. Ethyl acetate (58.34%) and aqueous (56.8%) extracts exhibited more antioxidant activity than the standard ascorbic acid (50.67%). The results revealed that the leaf extracts of Chromolaena odorata contains bioactive compounds having antimicrobial activity and so useful in human medicine.